Lamin A/C Acts as an Essential Factor in Mesenchymal Stem Cell Differentiation Through the Regulation of the Dynamics of the Wnt/β‐Catenin Pathway. Issue 10 (October 2015) - Bermeo, Sandra; Vidal, Christopher; Zhou, Hong; Duque, Gustavo
ABSTRACT Changes in the expression of lamin A/C, a fibrilar protein of the nuclear envelope, are associated with the cellular features of age‐related bone loss. Reduced expression of lamin A/C inhibits osteoblastogenesis while facilitating adipogenic differentiation of mesenchymal stem cells (MSC) in vitro and in vivo. In this study we investigated the regulatory role that lamin A/C plays on the essential elements of the Wnt/β‐catenin pathway, which are pivotal in MSC differentiation. Initially, we assessed the effect of lamin A/C gene (LMNA) overexpression on MSC differentiation while compared it to lamin A/C depleted MSC. Osteogenesis and gene expression of osteogenic factors were higher in LMNA‐transfected MSC as compared to control. Conversely, adipogenesis and expression of adipogenic factors were significantly lower in LMNA transfected cells. Nuclear β‐catenin was significantly higher (∼two fold) in MSC expressing higher levels of LMNA as compared to control with nuclear β‐catenin levels being significantly lower (∼ ‐42%) in siRNA‐treated MSC. Luciferase activity for β‐catenin‐mediated transcriptional activation was significantly higher in cells overexpressing LMNA. These data indicate that MSC overexpressing LMNA have higher osteogenic and lower adipogenic differentiation potential. In conclusion, our studies demonstrate that lamin A/C plays a significant role in the differentiation of both osteoblasts and adipocytes by regulating some of the elements of Wnt/β‐catenin signaling during early MSC differentiation. J. Cell. Biochem. 116: 2344–2353, 2015. © 2015 Wiley Periodicals, Inc.